Spain public meeting (leaflet)
042-0111-001 NORTH LONDON LABOUR SPAIN COMMITTEE SPAIN PUBLIC MEETING at FRIENDS' MEETING HOUSE, Euston Road, N.W.1 on Monday, SEPT. 27th, 1937 at 8 p.m. Speakers: C.R. ATTLEE, M.P. HERBERT MORRISON, M.P. D.N. PRITT, K.C., M.P. DR. S.L. JEGER, L.C.C. NURSE THORA SILVERTHORNE (Of the first Spanish Medical Aid Unit) ADMISSION FREE RESERVED SEATS 6d. Tickets obtainable from Local Labour Parties or from the Organisers, 9, Adelaide Road, N.W.3. COLLECTION IN AID OF SPANISH MEDICAL AID COMMITTEE. Speedee Press Services Ltd. (T.U.), 112, Fetter Lane, E.C.4. 292/946/42/111